Nutritive Value of Barley Fodder Grown in a Hydroponics System - Abdullah, Azila (2001)
A series of experiments were conducted to evaluate barley fodder (BF) as a feed for ruminants. Barley seeds were grown in a specially designed and controlled environment cabin at 15 - 18°C. The first experiment was conducted to germinate barley seeds from day 0 (dO) to day 10 (dIO, n=ll) and samples were collected daily for chemical composition analysis. In the second experiment, the rumen simulation technique (RUSITEC) was used to measure the in vitro dry matter (DM) and crude protein (CP) digestibility and the volatile fatty acids (VF A) produced by BF at different times. The nylon bag technique was also used to measure the DM degradability of BF in the rumen of cattle at 2, 4, 8, 12, 24 and 48 hours. The third experiment on the intake and digestibility of eight-day old BF was measured by an in vivo technique, using four bucks. The fourth experiment involved the measurement of rumen fluid parameters (pH, ammonia and VFA) in three rumen fistulated bucks that were fed on eight-day old BF ad libitum. The CP, organic matter (OM), ether extract (EE), neutral detergent fibre (NDF), acid detergent fibre (ADF) and crude fibre (CF) contents of BF from d1 to d10 increased, but the DM content decreased with the age of BF. DM content at d7 and d8 were 16 and 18% while CP content were 12 and 13% respectively. The amount of calcium (Ca), phosphorus (P) and Nitrate (N03) did not change significantly throughout sprouting time. The in vivo, in vitro and in sacco DM degradability studies showed that 80 to 100% DM loss for BF harvested on d7 to dW. DM intake was lower in the third experiment although digestion coefficient (DC) of BF was very high (98%). This condition was probably due to the abnormal growth of BF during the experimental period. Rumen fluid pH was 5.9-6.0 and ammonia-N (NH3-N) content was 7.0 to 8.8 mg/mL. Total fatty acids production was 70 to 1 00 mmoVL between two and eight hour of collection. The acetic:propionic:butyric ratios were 58:36:1.3, 68:25:2, 61:35:1.2, 64:33:0.7 and 65:32:1 at 0, 2, 4, 6 and 8 hours, respectively. Overall results showed that VFA and ammonia-nitrogen (NH3-N) were produced at a minimum level when BF was given ad libitum although the digestibility was higher in both in sacco and in vitro studies. BF should be given at different levels in order to get optimum pH, VFA and NH3-N production.